Young H.C. Andersen and His Friend Victor - Capezzone, Thierry 1963-; Rybka, Jan, 1979-; Feeloo (Chicago, Illinois : World Book Inc., 2020)
"In this comic-book adventure, a young Hans Christian Andersen travels to Paris and clashes with the famed storyteller Victor Hugo"--
Ages 5-12.
Keywords: Andersen, H. C; 1805-1875 -- Childhood and youth; Juvenile fiction; Andersen, H. C; 1805-1875 -- Childhood and youth; Fiction; Hugo, Victor, -- 1802-1885 -- Fiction; Adventure and adventurers -- Fiction